3x-16=x+89

Simple and best practice solution for 3x-16=x+89 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-16=x+89 equation:


Simplifying
3x + -16 = x + 89

Reorder the terms:
-16 + 3x = x + 89

Reorder the terms:
-16 + 3x = 89 + x

Solving
-16 + 3x = 89 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-16 + 3x + -1x = 89 + x + -1x

Combine like terms: 3x + -1x = 2x
-16 + 2x = 89 + x + -1x

Combine like terms: x + -1x = 0
-16 + 2x = 89 + 0
-16 + 2x = 89

Add '16' to each side of the equation.
-16 + 16 + 2x = 89 + 16

Combine like terms: -16 + 16 = 0
0 + 2x = 89 + 16
2x = 89 + 16

Combine like terms: 89 + 16 = 105
2x = 105

Divide each side by '2'.
x = 52.5

Simplifying
x = 52.5

See similar equations:

| 2n^2=-14+11n | | 2e^3x-4+8=56 | | 2y+4=8y-8 | | 5=-2n+8+3 | | x/6=10.5 | | -8(-8+n)-6(7n-3)=54 | | 3n^2-1=-2n | | 6(2m-5)+3m=15m-10 | | a=3.14(5625) | | 9x+15=-36 | | 9r-7r=12 | | -3(7b-5)=99 | | 1/2,-2,1 | | -34=4a-2a | | h-3.5=7.6 | | h^2=49 | | 5x^2+13x+12=x+5 | | -2(11-9x)-2(x-1)=11x | | 6=5(x)+24 | | cy+fy=j | | h^2=4i | | 3*y-10=y | | 18/b=6 | | 6=(15/2)x | | 1.95x+2.50=27.46 | | -8w+3=-29 | | y=1500(4)-.15 | | h=-16t^2+10t+25 | | 2p-6=8+5(1p+9) | | 2x^2=3x-12 | | y=1500x-.15 | | 250+2.8x= |

Equations solver categories